PENILAIAN KELAYAKAN USAHA KONVEKSI UMKM BERKAT SELAKU MITRA BINAAN UPT TEKSTIL DIVISI PRODUK PAKAIAN JADI DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SUMATERA SELATAN BERDASARKAN ASPEK KEUANGAN UNTUK MENGEMBANGKAN STRATEGI BISNIS - Dwi Aneli; Muhammad Yusuf (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2016)
The research is conducted to evaluate some illustration criteria about the eligibility of a business in UMKM Berkat as a partner of UPT Textile for confection division in Dinas Perindustrian dan Perdagangan of South Sumatera based on financial aspect. Research methodology is used both of quantitative and qualitative research.  This analysis is required at least seen by Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit Cost Ratio (Net B/C). Factors considered are the estimated investment, working capital, operating costs, maintenance and revenue forecasts The data were analyzed by reviewing the theory developed by R.A Supriyono (2010), Yacob Ibrahim (2009). There are five criterias in evaluating the eligibility of a business. The calculation by using those method which is Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Indeks (PI) dan Break Even Point (BEP). According to the result of businesseligibility analysis find that; Payback Period can returned the capital about three years and six months (3,24 years), Net Present Value obtained in a positive (+) value which is Rp.273.597.150, Internal Rate of Return is on 37% and 38%, Profitability Indeks is 2,28 and Break Even Point is Rp. 106.550 and 21 units. By the value of the results can be concluded that UMKM Berkat as as a partner of UPT Textile for confection division in Dinas Perindustrian dan Perdagangan of South Sumatera is eligible established.